Análisis de la Directiva Europea de whistleblowing y principales retos de la nueva regulación. El caso de España - Torrent I Santamaria, Josep Maria (2020)
With the approval of the European Directive 1937/2019 on October 23rd, that the countries of the European Union are required to transpose no later than two years after its entry into force, all companies, as well as public entities with more than fifty workers, must enable a whistleblower channel. The purpose of this article is to synthesize the main novelties that this norm introduces, highlighting the importance of initially reaching an agreement on the very definition of the informant. In Spain, the lack of regulation of this figure so far has led the doctrine to search for solutions in the general theory of crime, as well as in other disciplines of law, in order to solve the difficulties that have arisen with the use of reporting channels by companies that chosed to incorporate a compliance program. Finally, we will point out some of the problems arising from the transposition of the Directive from the perspective of its compatibility with the system of rights and guarantees that rule the criminal process. Along these lines, a harmonization of the newly released whistleblower’s apparent exemption from liability with the current Penal Code is proposed, also focused on the need to provide guarantees to internal investigations to preserve the validity of the evidence that may be obtained by them.